Research collaboration towards improved animal and human health: Report of a workshop between the International Livestock Research Institute and partners from Germany, 27 February–1 March 2018 - International Livestock Research Institute (International Livestock Research Institute, 2018)
Collaboration between the International Livestock Research Institute (ILRI) and partners from Germany dates back to the early days of ILRI’s predecessors, the International Laboratory for Research on Animal Diseases and the International Livestock Centre for Africa. Since the 1980s, this joint research has focused on the control of trypanosomiasis in livestock (including camels) across the vast ‘tsetse belt’ of Africa and on increasing animal productivity through breeding and improved nutrition.